Stigma or sympathy? attributions of fault to hate crime victims and offenders - Lyons, Christopher J.
This study investigates the influence of social status or attributions of blame in specific instances of hate crime. Two theoritical explanations for the impact of offender's and victim's social status characteristics on evaluations of hate crimes are examined. The stigma perspective suggest that the public will deride minority-status individuals,whereas the sympathy perspective implies that the public will be sympathetic to members of minorities. Results from a factorial survey reveal mixed support for both perspectives, depending on the victim's status (race,gender, or sexual orientation). Respondents appear especially sensitive to racial status asymmetry, blaming white offenders more than black offenders and black offenders and victims less than white victims, but sympathy is not evident for gay and lesbian victims. Results also suggest that gay and lesbian victims are held more accountable for their actions than heterosexual victims and that respondent's attitudes shape attributions of blame.